Algebras with Fuzzy Operations - Davidov, S.; Hatami, J. (Mathematical Problems of Computer Science, 2021)
In the present paper, we introduce algebras with fuzzy operations. The problem of development of algebras with fuzzy operations is formulated in [1]. We consider fuzzy operations instead of ordinary functions in structure of algebras.